I will assume that you meant:
(x+4)/(-3x^2+12x+36) factor the denominator...
(x+4)/(-3(x^2-4x-12))
To factor a quadratic of the form ax^2+bx+c you need to find two values, j and k, which satisfy two conditions...
jk=ac=-12 and j+k=b=-4 so j and k must be 2 and -6 and the factors are then:
(x+2)(x-6) so we are now left with:
(x+4)/(-3(x+2)(x-6))
The only restriction on this function is that division by zero is undefined, so x cannot equal -2 or 6
286 ÷ 5 1/2 hours = 286 ÷ 5.5 = 52 final answer
Answer:
The diagonals of a rectangle are always congruent
Answer:
Kennedy did not distribute the 3 to the numbers in the parentheses.
Step-by-step explanation:
The simplified expression should be -3x+24.